Peningkatan Kapasitas Kader Posyandu Pada Pemberian MP-ASI Berbasis Pangan Lokal Di Kecamatan Ubud Kabupaten Gianyar - I G.A.Ari Widarti; A.A.Gde Raka Kayanaya (Poltekkes Kemenkes Denpasar, 2019)
This community service is carried out by providing counseling and demonstration/practice of processing MP-ASI to posyandu cadres who are still active in Sayan and Singakerta Villages, Ubud sub-district, Gianyar district, which is the working area of UPT Kesmas Ubud II. Community service is carried out for three months starting from August to October 2018. During the service period, the number of targets was given as much as 30 people. Observations were obtained in the form of knowledge data, the attitude of pregnant women about MP-ASI and evaluation of the practice of preparation and processing of MP-ASI from local foods. The data obtained are presented and processed descriptively. Based on observations obtained the level of target knowledge with good categories, and enough before being given counseling each of 93.30%, 6.70%, and there were no targets with fewer knowledge categories. After counseling, all targets (100%) have a good level of knowledge. Whereas the mother cadre's attitude towards MP-ASI have an increase in the proportion of answers that agree on the target, namely from 76.70% to 93.33%. More intensive counseling needs to be done through more varied methods and media, so that goal understanding is more optimal.Keywords: Posyandu Cadre, ASI Complimentary Food